Environmental management practices (EMPs) for sustainable development in Malaysian food processing SMEs - Latip, Malisah; Mohamed, Zainal Abidin; Sharkawi, Ismawati; Sharifuddin, Juwaidah (Academic Inspired Network, 2018)
The interest on environmental management has been notably increasing in the past few years and nowadays is considered to be a mainstream challenge for organizations. The involvement of SMEs in environmental friendly practices can be of particular significant as their total impact can be huge, caused by cumulative effects associated to large number of enterprises. Despite the fact that there is a growing awareness of the environmental impact caused by SMEs, this is not transformed into practice. SMEs consider themselves as too small to cause big impact to the environment. This can be seen from the slow adoption rate of formal environmental management system among SMEs in Malaysia. This study endeavours to determine the factors influencing intention to adopt EMPs among food processing SMEs by integrating two theories namely; (i) Technology-Organization-Environment (TOE) framework and (ii) Theory of Planned Behavior (TPB). Drawing upon the both theories, this study groups the determinant factors of TOE model into technological, organizational and environmental contexts; while the determinants factors of TPB are attitude, subjective norm and perceived behavioral control. The data were collected via email-based survey, which was sent to 633 owner-managers of food SMEs in Malaysia, and 118 usable samples were analyzed. Exploratory factor analysis (EFA) was used to identify latent factors affecting the intention to adopt EMPs. The results of EFA revealed eight factor solutions with eigenvalues greater than 1.0. Generally, these factors explained 83.45 percent of the total variance, which is considered as satisfactory. KMO measure of sampling adequacy was 0.910 indicating sufficient intercorrelations. Results suggest that the dominance of owner-managers’ attitude (total variance: 47.72%) as the most important factor affecting the intention to adopt EMPs.